2015
DOI: 10.1016/j.ijscr.2015.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Management of pregnancy associated breast cancer with chemotherapy in a developing country

Abstract: HighlightsThe use of chemotherapy in our series for pregnancy associated breast cancer was successful with resulting healthy babies.Chemotherapy was done from the second trimeater.The choice of drugs were doxorubicin and cyclophosphamide administered by a slow infusion protocol.The babies did not require ICU care.Breast conservation was successfully used in one of the cases who is clinically disease free 5 years post diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Some of such areas are: CT images, growth factor levels in incident breast cancer, hormone receptor status, cytokine circulation, secretagogue users in breast cancer treatments, chemokine levels, breast cancer and diabetes mellitus co-infection and treatment, breast cancer and HIV treatment, breast cancer and pregnancy. Others are: proteome analysis, risk factors analysis, breast examination, screening, management and breast cancer awareness, epidemiology, risk assessment tools, treatment options: radiotherapy treatment versus chemotherapy, survival analysis, breast cancer subtypes, biomarkers, socio-cultural barriers to treatment, socio-demographic factors and alternative medicine approach, genetic risk, dietary patterns, early diagnostics and treatment and others [1] , [2] , [3] , [4] , [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] .…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%
“…Some of such areas are: CT images, growth factor levels in incident breast cancer, hormone receptor status, cytokine circulation, secretagogue users in breast cancer treatments, chemokine levels, breast cancer and diabetes mellitus co-infection and treatment, breast cancer and HIV treatment, breast cancer and pregnancy. Others are: proteome analysis, risk factors analysis, breast examination, screening, management and breast cancer awareness, epidemiology, risk assessment tools, treatment options: radiotherapy treatment versus chemotherapy, survival analysis, breast cancer subtypes, biomarkers, socio-cultural barriers to treatment, socio-demographic factors and alternative medicine approach, genetic risk, dietary patterns, early diagnostics and treatment and others [1] , [2] , [3] , [4] , [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] .…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%
“…While the description of said treatment was not identified, this study did validate that therapeutic abortion or termination of pregnancy was not necessary for all patients prior to initiating cancer treatment [8]. Not only is termination not necessary, but some studies have also demonstrated a lack of survival benefit to the patient with termination of pregnancy prior to initiation of cancer treatment [1][2][3][4]7].…”
Section: Discussionmentioning
confidence: 75%
“…Adriamycin and cyclophosphamide are generally well tolerated in pregnancy and suggested to be two of the chemotherapy drugs of choice for treatment of PABC in a recent expert opinion published by Lambertini, et al in which he reviews the literature to date which is admittedly limited of the safety profile of these drugs during pregnancy. The most common medical side effect of these drugs is myelosuppression in both the mother and fetus [3,5,7,9,12,13]. In one study, Rouzier demonstrated the chemosensitivity to these drugs was the same in tumors of PABC and tumors of non-pregnancy associated breast cancers [3,14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other protocols have been reported to produce different fetal growth outcomes. Sule and Ewemade reported that doxorubicin and cyclophosphamide administration for breast cancer treatment during the second trimester in a developing country did not affect birth weight [ 39 ]. Furthermore, Ring et al retrospectively described the outcomes of 28 pregnant patients treated with chemotherapy for breast cancer at 5 hospitals in London.…”
Section: Chemotherapy For Breast Cancer During Pregnancymentioning
confidence: 99%